Analisis Pengaruh Ekspor dan Impor Terhadap Cadangan Devisa Indonesia - Andriandita Wijayanto; Nona Maria Engelina L (Fakultas Ekonomi Universitas Yos Soedarso, 2022)
Indonesia is one of the developing countries, where Indonesia implements an open economic system. In an open economic system, relations between one country and another, both bilateral and multilateral, will create transactional activities. This transactional relationship requires a means of payment in the form of foreign exchange taken from foreign exchange reserves. Foreign exchange reserves are defined as a number of foreign currencies reserved by the central bank (Bank Indonesia) for the purpose of financing development and overseas obligations such as import financing and other financing to foreign parties. One very important monetary indicator that shows the strength and weakness of a country's economic fundamentals is foreign exchange reserves. Adequate foreign exchange reserves are one of the guarantees for achieving a country's monetary and macroeconomic stability (Tambunan, 2001). The more active a country trades, the more foreign exchange it needs. Foreign exchange is also obtained from foreign aid either through foreign debt or through grants or often called capital outflow. Foreign exchange is used in the construction of industrial projects and projects such as roads, bridges, wharves, airports and terminals. Foreign exchange reserves are an important source of funding used by Indonesia to carry out national development, which are kept and accounted for by Bank Indonesia. The country's foreign exchange reserves are obtained from trading activities between countries. Trade between countries occurs because a country is unable to meet its needs, namely producing goods or services due to limited and scarce resources, both natural resources and human resources, so that this can encourage a country to carry out trade known as export and import activities. The goal to be achieved in this research is to find out how exports and imports affect Indonesia's foreign exchange reserves.